Extracto de hojas de ortiga (Urtica dioica) como agente antimicrobiano aplicado en una longaniza artesanal en el cantón Chone - Zambrano Muñoz, Adrean Enrique (2022)
The present study evaluated the extract of nettle leaves (Urtica dioica) as an antimicrobial agent applied in an artisan sausage in a microenterprise in Chone canton. Once the nettle leaf extract was obtained, we worked with 5 treatments, 3 repetitions and a control, for treatments T1, T2, T3 and T4 concentrations of 1.0%, 1.5%, 2.0% and 2.5% were used, respectively. The microbiological parameters of mesophilic Aerobes, Escherichia coli, Staphylococcus aureus and Salmonella included in the NTE INEN 1338, 2012 standard were evaluated; once the microbiological results were obtained, they were interpreted using the binary logistic regression statistical technique. An extract of nettle leaves of dark green color was obtained, the smell of ethanol predominated and with a fluid liquid texture. It was found that the best treatment was T3, this had a greater effect on the E Coli variable, however, the dosage was not sufficient to inhibit mesophilic Aerobes, Staphylococcus aureus and Salmonella; due to the fact that no treatment complies with the microbiological parameters established in the NTE INEN 1338 2012 standard, the sensory analysis of the organoleptic characteristics of the longaniza could not be determined. It is concluded that treatment 3 corresponding to 2% of nettle leaf extract was the one that had the greatest effect on the E Coli variable, although its dosage was not sufficient to inhibit the other bacteria.